Dynamic argumentation in abstract dialogue frameworks - Marcos, Maria Julieta (2011)
In this work we present a formal model for collaborative argumentation based dialogues by combining an abstract dialogue framework with a formalism for dynamic argumentation. The proposed model allows any number of agents to interchange and jointly build arguments in order to decide the justification status of a given claim. The model is customizable in several aspects: the argument attack relation and acceptability semantics, the notion of relevance of contributions, and also the degree of collaboration are selectable. Important properties are ensured such as dialogue progress step by step, completeness of the sequence of steps, and termination. Under the higher degree of collaboration, the dialogue constitutes a sound and complete distributed argumentation process. © 2011 Springer-Verlag.